EVOLUTION OF DIDACTICSOFTWARE RIDNOMOVNOYI UKRAINIAN EDUCATION IN CANADA AND THE USA - Romaniuk, Svetlana Z. (Educological discourse, 2014)
The paper studies the features of the native language in the Ukrainian diaspora in Canada and the United States and its training and methodological support; analysis of textbooks and manuals on Ukrainian language native schooling in the diaspora, their didactic support and possible use in the educational process; the structure, content and methodical manuals for machine learning Ukrainian language (linguistic system of exercises, tasks, illustrations to the text, the definition of linguistic concepts); textbook Ukrainian teachers in Canada and the United States are seen as an important means of improving the efficiency of learning the native language and the formation of national and patriotic feelings Ukrainian Foreign; deserves further study their use in the educational process native schooling diaspora.